Estimasi dan Komunikasi Data Penduduk Umur Sekolah Berdasarkan Proyeksi Penduduk Indonesia 2020-2050 Hasil Sensus Penduduk 2020 - Prasojo, Ari Purwanto Sarwo (Politeknik Statistika STIS, 2024)
Education inequality is a challenge in human development in Indonesia. Providing and communicating data on school-age population projections is important to achieve equitable quality education. This article estimates the school-age population based on Indonesia’s 2020-2050 population projections from the 2020 Population Census (SP2020) and develops an open-source interactive visualization application in the form of the R library “estPUSek” to explore these dynamics in 34 provinces. The estimation used the Sprague method, which proved accurate based on testing with Long Form Population Census 2020 (LF SP2020) data. The